PERAN KELOMPOK SADAR WISATA DALAM PEMBERDAYAAN USAHA MIKRO, KECIL, DAN MENENGAH KAMPUNG HERITAGE KAYUTANGAN KOTA MALANG - Ocha Aulia Widuri; Ananta Prathama (Halu Oleo University, 2025)
This study aims to increase the independence of Micro, Small and Medium Enterprises (MSMEs) actors in Kayutangan Heritage Village, Malang City. This research uses the theory of community empowerment efforts by Mardikanto and Soebiato (2013), including efforts to create (enabling), strengthen (empowering), and protect (protecting). The research method used is a descriptive qualitative approach with data collection techniques obtained from observation, interviews, and documentation. The results showed 1) efforts to create through encouragement or motivation to MSME actors to sell traditional products and create MSME associations to assist MSME actors in increasing their production, 2) efforts to strengthen potential through training and facilitating MSME actors to have a digital payment system, 3) efforts to protect facilitate the making of business legality including NIB and P-IRT which are already owned by MSME actors. Nevertheless, there are still challenges such as the absence of MSME associations for other fields, the absence of post-training assistance, and limited training quotas. Therefore, it is hoped that in the future, Pokdarwis will also pay attention to other MSME fields, as well as additional quotas and post-training assistance.